THE EFFECT OF ELIGIBILITY CONTRAINDICATIONS ON THE CIVIL CODE (A COMPARATIVE STUDY WITH ISLAMIC JURISPRUDENCE) - AT Sara Kadhim Rahi (Scholar Express Journal, 2022)
For the validity of any legal action requires the availability of the will, which is the main driver of legal and legitimate actions, and therefore the legislator requires that whoever issues it should have a certain share of mental powers, and the person may be fully qualified, yet he has conditions that prevent him from undertaking the actions himself or alone For this reason, the law decides to appoint a person to undertake these actions or assist him in carrying out these actions, and the legislator’s failure to organize such cases, as there is no special legal regulation of civil barriers. Eligibility, therefore, the Iraqi legislator must have made the impediments to eligibility within a special section called the impediments to eligibility to distinguish them from others
Keywords: Cinema; art; director; symbol